1991
DOI: 10.1002/j.1460-2075.1991.tb07725.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of a cDNA encoding the rabbit ileal villus cell basolateral membrane Na+/H+ exchanger.

Abstract: A cDNA clone encoding a rabbit ileal villus cell Na+/H+ exchanger was isolated and its complete nucleotide sequence was determined. The cDNA is 4 kb long and contains 322 bp of 5′‐untranslated region, 2451 bp of open reading frame and 1163 bp of 3′‐untranslated area, with 70%, 91% and 40% identity to the human sequence, respectively. Amino acid sequence deduced from the longest open reading frame indicated a protein of 816 residues (predicted Mr 90,716) which exhibits 95% amino acid identity to the human Na+/H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
96
0
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(98 citation statements)
references
References 31 publications
0
96
0
2
Order By: Relevance
“…Cells were transfected with NHE3-GFP cDNA (or with pEGFP-N3 vector) using LipofectAMINE (Life Technologies, Inc.) according to the manufacturer's instructions. The cell population expressing NHE3-GFP was initially enriched using the acid selection technique (18). Stable clones expressing functional NHE3-GFP (PS120-E3G cells) were subsequently isolated using dilutional cloning, propagated in a large scale culture, and frozen in liquid nitrogen.…”
Section: Engineering Of Nhe3-gfp Expressionmentioning
confidence: 99%
“…Cells were transfected with NHE3-GFP cDNA (or with pEGFP-N3 vector) using LipofectAMINE (Life Technologies, Inc.) according to the manufacturer's instructions. The cell population expressing NHE3-GFP was initially enriched using the acid selection technique (18). Stable clones expressing functional NHE3-GFP (PS120-E3G cells) were subsequently isolated using dilutional cloning, propagated in a large scale culture, and frozen in liquid nitrogen.…”
Section: Engineering Of Nhe3-gfp Expressionmentioning
confidence: 99%
“…Since the cloning of NHE1 by Sardet et al (1989), three additional members of the mammalian gene family have been identified by our group (Tse et al 1994a;Tse et al 1993b;Tse et al 1991) and by Orlowski and Shull (Orlowski et al 1992;Wang et al 1993). We named these clones in the order of their molecular identification as NHE1, NHE2, NHE3, NHE4, etc.…”
Section: Na-h Exchanger Gene Familymentioning
confidence: 99%
“…Orlowski et al (7) have identified three closely related Na+/H+ exchangers in rat tissues, NHE-1, NHE-3, and NHE-4, by screening cDNA libraries from the stomach, colon, brain, and spleen. Similarly, Tse et al (8,9) have identified two isoforms, NHE-1 and NHE-3, in rabbit by screening an ileal cDNA library. These isoforms exhibit differences in sequence homology, tissue expression, and molecular mass (7)(8)(9).…”
mentioning
confidence: 95%
“…Similarly, Tse et al (8,9) have identified two isoforms, NHE-1 and NHE-3, in rabbit by screening an ileal cDNA library. These isoforms exhibit differences in sequence homology, tissue expression, and molecular mass (7)(8)(9).…”
mentioning
confidence: 95%